2001
DOI: 10.1007/pl00001936
|View full text |Cite
|
Sign up to set email alerts
|

Root Resorptions in Upper First Premolars after Application of Continuous Torque Moment Intra-Individual Study

Abstract: The analysis in a scanning electron microscope (Jeol 6100, at 10-15 kV) revealed many resorption lacunae in the root surface, mainly on the lingual side in the apical third of the roots. Resorption processes were also observed on the buccal root surface in the cervical third. All experimental teeth showed resorption areas. Teeth which had been moved for a longer time period and with a higher magnitude of applied moments showed a higher degree of root resorption in width as well as in depth. Higher magnitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
2
19

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 24 publications
7
64
2
19
Order By: Relevance
“…Apical RR is clinically significant, as RL can accumulate at the apical region and can lead to permanent root shortening and a reduced crown/root ratio. 38,39 Our study also highlighted the deleterious effect of torque on OIRR, as previously reported 8,9 Since this 4-week period corresponds to the usual time interval between two orthodontic appointments, further activation of orthodontic force or orthodontic appliances might greatly increase the risk of OIRR. LIPUS application, however, was not able to completely heal the resorption craters during this time.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Apical RR is clinically significant, as RL can accumulate at the apical region and can lead to permanent root shortening and a reduced crown/root ratio. 38,39 Our study also highlighted the deleterious effect of torque on OIRR, as previously reported 8,9 Since this 4-week period corresponds to the usual time interval between two orthodontic appointments, further activation of orthodontic force or orthodontic appliances might greatly increase the risk of OIRR. LIPUS application, however, was not able to completely heal the resorption craters during this time.…”
Section: Discussionsupporting
confidence: 74%
“…10 Bartley et al 8 applied 2.85 N/mm (285 g/mm) of torque and observed more resorption at the apical level than at the middle and cervical level. Casa et al 9 applied 6 N/mm of torque and reported severe root resorption at the apex. Apical RR is clinically significant, as RL can accumulate at the apical region and can lead to permanent root shortening and a reduced crown/root ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was one distinct fact that almost all the teeth had some degree of root resorption. The repair of the resorption can start after the force discontinued or decreased (38,39). In our study, first premolars were extracted at the end of the expansion period to eliminate repair process.…”
Section: Discussionmentioning
confidence: 99%
“…This aspects are as follows: treatment duration (Casa et al, 2001;Fox, 2005;Levander & Malmgren, 1988;Otis et al, 2004;Paetyangkul et al, 2011;Sameshima & Sinclair, 2004;Segal et al, 2004), magnitude of the applied forces (Barbagallo et al, 2008;Bartley et al, 2011;Casa et al, 2001;Chan et al, 2005;Harris et al, 2006;Paetyangkul et al, 2011), direction of tooth movement (Barbagallo et al, 2008;Han et al, 2005) amount of apical displacement (Fox, 2005;Segal et al, 2004), force application method (continuous vs. intermittent) Faltin et al, 2001), type of appliance Pandis et al, 2008) and treatment technique (Bartley et al, 2011;Beck & Harris, 1994;Janson et al, 1999;Marques et al, 2010;Pandis et al, 2008;Parker & Harris, 1998;Scott et al, 2008).…”
Section: Orthodontic Treatment-related Factorsmentioning
confidence: 99%